Effectiveness of Problem-Based Learning Models in Improving Students' Collaborative Ability on Practical Activities of the Solution Colligative Properties - Fitriyah, Isnanik Juni; Muqoyyidin, Andik Wahyun; Aprilia, Septi; Wati, Rohma; Ramadhan, Umi Laila (Universitas Negeri Malang, 2024)
The study aims to evaluate the effectiveness of the Problem-based Learning model in improving the students' ability to collaborate on practical activities related to the solution colligative properties. The research design uses quasi-experimental methods with control groups and experiments. The study sample consisted of 60 XI IPA class students selected using purposive sampling techniques, with 30 students in the experimental group and 30 in the control group. The research instruments include a test of collaborative abilities, a sheet of observations on collaborative activities, and an elevator of student responses. The results showed that the average pre-test scores of students' collaboration ability in experimental and control groups were relatively the same. Still, there was a significant improvement in the experimental group's post-test score after applying the Problem-Based Learning model. The pair t-test results showed a substantial improvement in both groups, but the increase in the experimental group was significantly higher (t(30) = 12.45, p < 0.05) compared to the control group (t(30) = 3.21, p < 0.05). Independent t-tests showed significant differences between the experimental and control groups after treatment (t(60) = 6.34, p < 0.05). Observations during the practice showed that students in the experimental group were more active in communicating, sharing tasks, collaborating, and solving problems than in the control group. In addition, the student response raise showed that the majority of students responded positively to the Problem-Based Learning model, with a high average score on interesting and enjoyable aspects (4.5), boosting motivation (4.6), facilitating the understanding of concepts (4.4), and enhance the ability to collaborate (4.7).